Maria da Graça L. Castro Pinto. A escrita. O papel da universidade na sua otimização. Porto: Faculdade de Letras da Universidade do Porto, 2014. 247 pp. ISBN 978-989-8648-30-3 - Duarte, Isabel Margarida (Linguarum Arena, 2015)
.